See discussions, stats, and author profiles for thisCandida colonization of the vagina of HIV-seropositive pregnant women and their seronegative counterparts at selected health-care centers in Akure, Ondo State, Nigeria - Ebhodaghe, Blessing Itohan; Ako-Nai, Kwashie Ajibade; Aderoba, Adeniyi; Anderson, Winston A; Kassem, Olakunle O. (Annals of Tropical Medicine and Public Health, 2023)
Annals of Tropical Medicine and Public Health.Vol. 9,No. 6,p. 381-391